INDEKS KOLAPSIBILITAS (CI) SEBAGAI PREDIKTOR HIPOTENSI PADA PASIEN DENGAN ANESTESI UMUM - Pranata, I Made Harry; Adi, Made Septyana Parama; Suarjaya, I Putu Pramana; Kurniyanta, Putu (E-Jurnal Medika Udayana; Vol 12 No 10 (2023): E-Jurnal Medika Udayana, 2023)
Intraoperative hypotension (IOH) is important to identify early because it is associated with high morbidity and mortality in old age. Ultrasonographic measurement of the inferior vena cava collapsibility index (IVCCI) can detect volume responsiveness in circulatory shock. The purpose of this study was to examine the collapsibility index (CI) as a predictor of hypotension in patients under general anesthesia. This study was an observational cross-sectional design in adult patients who underwent elective surgery under general anesthesia at Sanglah General Hospital from December 2021 to January 2022 using a consecutive sampling technique. Immediate postinduction changes in systolic and mean blood pressure were compared. The performance of the IVC CI as a diagnostic tool for predicting hypotension (systolic pressure?<?90?mmHg or a???30% drop from the baseline) was evaluated by ROC curve analysis. At the point of collapsibility index (CI) ? 47, there were 29 patients (96.7%) with hypotension. At the point of collapsibility index (CI) < 47, there was 1 patient (3.3%) with hypotension and 24 patients (100%) without hypotension. The cut-off level of collapsibility index (CI) is obtained with the Receiver Operating Curve (ROC) curve, below 0.985. The cut-off CI level for hypotension was 47.0 with a sensitivity of 96.7% and specificity of 100%. There is a significant relationship between IVC CI with a decrease in MAP before and after induction at 4,8, and 10 minutes (p<0,05). The collapsibility index (CI) 50 can be used as a predictor of the incidence of hypotension in patients under general anesthesia. Keywords : hypotension, collapsibility index, general anesthesia.